Trends in Architecture and Middleware of Radio Telescope Control System - Jun Li; Na Wang; Zhiyong Liu; Yining Song; Ning Li; Lingming Xu; Jili Wang (Advances in Astronomy)
The control system is the central control unit of the radio telescope. It is used to monitor, control, coordinate, and manage software and hardware systems so as to satisfy the requirements of high-precision control in astronomical observation of radio telescope. The control system architecture is the foundation for the implementation of the control system, which determines the stability, scalability, and maintainability of the control system. Furthermore, the architecture design of the control system is closely geared towards the technological development of radio telescope and computer software architecture. In this article, we analyze the characteristic of the control system of a radio telescope in various steps and discuss the development of their architecture and middleware framework. System architecture and middleware framework of control system also serve as a useful reference for the design of other radio telescope control systems.